PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT INDO BATAM EKATAMA - yeo, Fernando; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
This study aims to determine the effect of workload, work environment and training on employee performance in PT Indo Batam Ekatama. This research method is using quantitative research method. The technique of collecting data is by distributing questionnaires to 107 respondents. Data were analyzed using test of validity, reliability, normality, multicollinearity, heterokedastisitas, multiple linear regression analysis, t test and F test. Test results of coefficient of determination Adjusted R Square shows that workload, work environment and training variable are together providing 0.00 percent influence on employee performance variable. The results of this study indicate that partially workload has influence on employee performance, seen significant value 0.001 smaller than α value 0.05 and t value 3.417 bigger than t table 1.982 (H1 accepted), work environment has influence on employee performance because its significant value 0.000 smaller than α value 0.05 and t value 5.136 bigger than t table 1.982 (H2 accepted), training has influence on employee performance because its significant value 0.007 smaller than α value 0.05 and t value 2.763 bigger than t table 1.982 (H3 accepted), while workload, work environment and training are simultaneously has significant effect on employee performance because its significant value 0.000 smaller than α value 0.05 and f value 62.217 bigger than f table 3.08 (H4 accepted).